2022
DOI: 10.3390/ma15217676
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Optical Properties of CsPbBr3 Nanoplatelets through Cd2+ Doping

Abstract: Lead halide perovskite nanoplatelets (NPls) attract significant attention due to their exceptional and tunable optical properties. Doping is a versatile strategy for modifying and improving the optical properties of colloidal nanostructures. However, the protocols for B-site doping have been rarely reported for 2D perovskite NPls. In this work, we investigated the post-synthetic treatment of CsPbBr3 NPls with different Cd2+ sources. We show that the interplay between Cd2+ precursor, NPl concentrations, and lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…31 It should be noted that post-synthetic doping techniques have been mainly developed for cubic NCs, while relatively little research has been devoted to doping LHP nanostructures with more complex geometries. [32][33][34][35] In this regard, an urgent task is the development of universal, nondestructive and efficient methods for doping LHP nanostructures of various chemical compositions and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…31 It should be noted that post-synthetic doping techniques have been mainly developed for cubic NCs, while relatively little research has been devoted to doping LHP nanostructures with more complex geometries. [32][33][34][35] In this regard, an urgent task is the development of universal, nondestructive and efficient methods for doping LHP nanostructures of various chemical compositions and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Skurlov et al studied the influence of Cd 2+ doping on the two-photon absorption cross-section of CsPbBr 3 NPls using two-photon absorption-induced PL measurements (Figure 7c). [78] The post-synthetic treatment of the NPls allowed for finely tuning the doping ratio, which could be precisely monitored through a shift of the PL peak position. It was demonstrated that even a small fraction of inserted Cd 2+ ions induced a strong increase in the third-order nonlinear optical responses of perovskite NPls (Figure 7d).…”
Section: Applications Of Perovskite Npls and Dopingmentioning
confidence: 99%
“…Reproduced under CC BY license. [78] excitation. [90] Volume-normalized two-and three-absorption cross-sections enlarged from 183 to 1237 GM nm −3 (where GM is 10 −50 cm 4 •s•photon −1 ) and from 3.1 × 10 −79 to 2.24 × 10 −78 cm 6 •s 2 •photon −2 nm −3 , respectively, when the dimensionality of perovskite nanocrystals reduced from 3D to 2D.…”
Section: Applications Of Perovskite Npls and Dopingmentioning
confidence: 99%
“…Recently, impurity ion doping has gained significant attention for its ability to control the optical properties of perovskite NPLs. Among various dopants, Mn 2+ is the most widely investigated. It is well-established that the introduction of Mn 2+ ions into the host material leads to the emergence of new magnetic and optical properties. This process involves energy transfer from excitons within the host to Mn 2+ ions, resulting in the emission of orange-red light due to the spin-forbidden 4 T 1 → 6 A 1 Mn 2+ d-d transition.…”
Section: Introductionmentioning
confidence: 99%